(3GdLGeY GdUMjMs - (3eMeO Hf YjSi Hf ShQI Hf ehSi GdSdej GdHhZj GdJQePj, CHh YjSi ,J (B279 (3g` s
(3ChdgG (B:s
(3CHhGH GdCWYeI Yf QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3bGd QLd (B: (3jG QShd Gddg CYbdgG hCJhcd , Ch CWdbgG hCJhcd ? bGd (B: " (3CYbdgG hJhcd (B" (3hbO hVYfG gPG GdcJGH Ydi GdGNJUGQ fSCd Gddg GdfaY deG ajg , hCdG jLYdg YdjfG hHGdkG HQMeJg s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG JUMjMGJ hGdhQbI GdCNjQI HNW MOjK hYdjgG bQGAI Ydi GdEeGe eMeO Hf Ydi GdThcGfi SfI (B1220 (3g`s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3MOjK (B292) s
Keywords: (3GdMOjK h GdeUWdMs